AKUMULASI LOGAM CUPPRUM (Cu) DAN Z INCUM (Zn) DI PERAIRAN SUNGAI SIA K DENGAN MENGGUNAKAN BIOAKUMULATOR ECENG GONDOK (Eichhornia crassipes) - Suwondo '; Yuslim Fauziah; Syafrianti '; Sri Wariyanti (Biogenesis, 2005)
Have been conducted by a research to know the accumulation of metal Zincum (Zn) and Cupprum (Cu) in territorial water of  Siak River by using thyroid bioaccumulator Water hyasin (Eichhornia crassipes) what is conducted at month April-Juni  2004.  Method  used by that is survey with the technique of intake sampel  by purposive random sampling at 5 station.  Research parameter is content of metal Cu, Zn in thyroid and Water hyasin, temperature, brightness, dissolved oxygen, pH, nitrate and pospat. Analyze the data conducted descript result. The Result of research show concentration in territorial water Siak River metal Cu at height level at range 0.14-0,27 mg/1 and metal Zn low level at < 0.001 mg/1. Accumulation of metal Cu and Zn in Eichhornia crassipes height level categories, while at root 14,5-24,0 mg/1, at bar 8.0-16,0 mg/1 and at leaf 25 0-39,5 mg/1. Accumulation of metal Zn at root 74,0-189,5 mg/1, at bar 23,5-165,5 mg/l and at leaf 11,0- 9,0 mg/l.   Key words :  Metal Cu , Metal Zn, Bioaccumulator Eceng gondok (Eichhornia crassipes)